Functional Language Proficiency in Bilingual Children: A Conceptual Framework, Culturally Responsive Practice, and Measurement Approach. - Arizmendi, Genesis D. (Language, Speech & Hearing Services in Schools, 2025)
Purpose: Functional language proficiency is presented as a conceptual framework that builds upon cultural--linguistic assets in bilingually developing children and bridges the theory of natural translation, translanguaging, and language brokering practices. A novel task was developed based on this framework for quantifying Spanish--English bilingual children's functional language proficiency. The development, feasibility, face, and convergent validity of the Functional Language Proficiency (FLiP) task are detailed as part of this work, as well as its application and utility as a culturally responsive practice. Method: A conceptual framework and novel task were developed based on bilingual communication practices. This article details the conceptual framework and development process of the task, including considerations for cultural relevance, memory demands, linguistic complexity, and scoring procedures. The FLiP was administered to 90 Spanish--English learning Latino children in first, second, and third grade (30 per grade). Results: All 90 first-, second-, and third-grade children completed the task, generating an expectedly wide range of proficiency profiles across both languages. Importantly, 86% of the children reported that they had engaged in these language practices in their daily lives. There was strong interrater reliability (94%), and scores on the FLiP were positively correlated with measures of language sample analyses in both languages. Conclusions: The results of this study showed that the FLiP was an ageappropriate, asset-based, and culturally relevant task for measuring functional language proficiency in most Spanish--English school-age bilinguals. The role of functional proficiency is discussed, along with future research directions including validation, item analysis, and task refinement. Supplemental Material: https://doi.org/10.23641/asha.28946261